Ceramic-based oil-water separation membrane as well as preparation method and application thereof
By preparing a ceramic-based oil-water separation membrane, using Ti3C2Tx particles to composite with ZIF-62 and calcined and modified treatment, the problem of poor separation of oil-water separation membrane on oil-sliding wastewater and oil-in-water emulsification wastewater in the prior art is solved, and efficient oil-water separation effect is achieved.
Patent Information
- Application Number
- CN202411958916.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The existing oil-water separation membranes have poor oil-water separation effects on oil-water separation between oil-slipping wastewater and oil-in-water emulsified wastewater, especially for micro-nano-scale and stable oil-containing wastewater.
By using the preparation method of a ceramic base oil-water separation membrane, the Ti3C2Tx particles are peeled and then combined with ZIF-62, and after calcining and modification treatment, a ceramic base oil-water separation membrane with high separation performance is formed.
The oil-water separation efficiency of oil-water separation for oil-sliding wastewater and oil-in-water emulsified wastewater is significantly improved. The oil-water separation efficiency can reach 98.34% or above, and the flux is high, making it suitable for industrial applications.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of membrane separation, and in particular to a ceramic-based oil-water separation membrane and a preparation method and application thereof. Background Art
[0002] In recent years, the rapid development of industries such as petrochemicals, metal smelting, and chemical pharmaceuticals has produced a large amount of oily wastewater. The discharge of oily wastewater into the environment will lead to serious consequences. Therefore, the problem of oil-water separation has become a major challenge in the industry. Floating oil wastewater and oil-in-water emulsified wastewater are common types of oily wastewater. In the process of crude oil extraction and transportation, operational errors lead to the leakage of crude oil, resulting in a large amount of floating oil, which in turn forms floating oil wastewater. The amount of oil in the floating oil wastewater is large and it is difficult to handle. Oil-in-water emulsified wastewater mainly comes from industrial production processes such as refineries, petrochemicals, and metal manufacturing. Oil-in-water emulsified wastewater is also difficult to handle because it forms stable oil-in-water emulsion droplets.
[0003] Membrane separation technology has the advantages of low energy consumption, simple operation and high efficiency, and is widely regarded as an effective water treatment technology. However, the existing oil-water separation membrane has poor oil-water separation effect on floating oil wastewater and oil-in-water emulsified wastewater, especially micro-nano-scale and stable oil-containing wastewater. Summary of the invention
[0004] In view of this, the object of the present invention is to provide a ceramic-based oil-water separation membrane and its preparation method and application. The ceramic-based oil-water separation membrane prepared by the preparation method provided by the present invention has good oil-water separation effect in oil-in-water emulsified wastewater and floating oil wastewater.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a ceramic-based oil-water separation membrane, comprising the following steps:
[0007] Ti3C2T x The particles are peeled off to obtain Ti3C2T flakes. x ;
[0008] The Ti3C2T x , zinc salt and an organic solvent are mixed to obtain a zinc salt solution;
[0009] dissolving imidazole and benzimidazole to obtain a ligand solution;
[0010] The ligand solution is added to the zinc salt solution to perform an ultrasonic synthesis reaction to obtain ZIF-62 / Ti3C2T x Material;
[0011] The ZIF-62 / Ti3C2T x The material is calcined to obtain a g ZIF-62 / Ti3C2T x Material;
[0012] The a g ZIF-62 / Ti3C2T x The material, the modifier and water are mixed, and then modified and formed into a membrane in sequence to obtain the ceramic-based oil-water separation membrane.
[0013] Preferably, the stripping comprises: removing the Ti3C2T x The particles are dispersed in dimethyl sulfoxide and chemically intercalated to obtain the Ti3C2T x ; The Ti3C2T x The dosage ratio of the particles to dimethyl sulfoxide is 1 g: 10-20 mL; the chemical intercalation is carried out under stirring conditions, the stirring speed is 600-1200 rpm, and the time is 18-30 hours.
[0014] Preferably, the zinc salt comprises zinc acetate or zinc nitrate; the sheet Ti3C2T x The mass ratio of zinc salt to zinc salt is 5 to 15:1.
[0015] Preferably, the mass ratio of imidazole to benzimidazole is 3 to 12:1.
[0016] Preferably, the ultrasonic synthesis reaction has an ultrasonic frequency of 30 to 60 Hz, a temperature of 20 to 60° C., and a reaction time of 2 to 6 hours.
[0017] Preferably, the calcination temperature is 420-480° C., the heating rate to the calcination temperature is 5-15 K / min, and the holding time is 1-10 min.
[0018] Preferably, the modifier comprises one or more of carboxymethyl cellulose, polyethylene glycol and chitosan, wherein a g ZIF-62 / Ti3C2T x The mass ratio of the material to the modifier is 1 to 10:1;
[0019] The modification time is 12 to 36 hours.
[0020] Preferably, the film forming method is vacuum filtration, and the filter membrane used in the vacuum filtration is a CMC membrane, and the pore size of the CMC membrane is 0.45 μm.
[0021] The present invention also provides a ceramic-based oil-water separation membrane prepared by the preparation method described in the above technical solution.
[0022] The present invention also provides the application of the ceramic-based oil-water separation membrane described in the above technical solution in floating oil wastewater and oil-in-water emulsified wastewater.
[0023] The invention provides a method for preparing a ceramic-based oil-water separation membrane.
[0024] The preparation method provided by the present invention is based on Ti3C2T x Particles as raw materials, Ti3C2T x The particle surface contains many functional groups, which enable it to be well composited with other materials. x The particles were peeled off to obtain the Ti3C2T x (Layer Ti3C2T x single or multiple pieces), Ti3C2T x The lamellar structure increases the specific surface area and enables the subsequent in-situ synthesized ZIF-62 to be located in the lamellar Ti3C2T x In the layered structure of ZIF-62, Ti3C2T x The interlayers play a supporting role and stabilize Ti3C2T x interlayer spacing, preventing Ti3C2T x Excessive expansion in aqueous solution improves the separation performance of ceramic-based oil-water separation membranes. x The materials were calcined to form ZIF-62 / Ti3C2T x The ZIF-62 crystal particles in the material are vitrified to form vitrified ZIF-62 (a g ZIF-62), a g ZIF-62 further enhances its ability to resist lamellar Ti3C2T x The pillar support effect and inter-layer stability of a g ZIF-62 / Ti3C2T x The material is modified to further enhance the oil-water separation performance of the ceramic-based oil-water separation membrane. At the same time, the preparation method provided by the present invention uses simple raw materials and a simple process flow, which is conducive to industrial production.
[0025] Further, the present invention defines that the modifier includes one or more of carboxymethyl fiber, polyethylene glycol and chitosan, and one or more of carboxymethyl fiber, polyethylene glycol and chitosan are used to modify a g ZIF-62 / Ti3C2T x Material modification changes the hydrophilicity and hydrophobicity of the ceramic-based oil-water separation membrane and improves the oil-water separation efficiency of the ceramic-based oil-water separation membrane; moreover, the source of the modifier is relatively wide and the price is low. DETAILED DESCRIPTION
[0026] The present invention provides a method for preparing a ceramic-based oil-water separation membrane, comprising the following steps:
[0027] Ti3C2T x The particles are peeled off to obtain Ti3C2T flakes. x ;
[0028] The Ti3C2T x , zinc salt and an organic solvent are mixed to obtain a zinc salt solution;
[0029] dissolving imidazole and benzimidazole to obtain a ligand solution;
[0030] The ligand solution is added to the zinc salt solution to perform an ultrasonic synthesis reaction to obtain ZIF-62 / Ti3C2T x Material;
[0031] The ZIF-62 / Ti3C2T x The material is calcined to obtain a g ZIF-62 / Ti3C2T x Material;
[0032] The a g ZIF-62 / Ti3C2T x The material, the modifier and water are mixed, and then modified and formed into a membrane in sequence to obtain the ceramic-based oil-water separation membrane.
[0033] Unless otherwise specified, the raw materials used in the present invention are preferably commercially available products.
[0034] The present invention converts Ti3C2T x The particles are peeled off to obtain Ti3C2T flakes. x .
[0035] In the present invention, the peeling preferably includes: removing the Ti3C2T x The particles are dispersed in dimethyl sulfoxide and chemically intercalated to obtain the Ti3C2T x In the present invention, the Ti3C2T xThe dosage ratio of particles and dimethyl sulfoxide is preferably 1g:10-20mL, and is preferably 1g:10mL, 1g:15mL or 1g:20mL. In the present invention, the chemical intercalation is preferably carried out under stirring, and the stirring speed is preferably 600-1200rpm, and is preferably 600rpm, 700rpm, 800rpm, 900rpm, 1000rpm, 1100rpm or 1200rpm; the time is preferably 16-32h, and is preferably 16h, 18h, 24h, 30h or 32h; after the chemical intercalation, the present invention preferably further comprises: centrifuging the obtained chemical intercalation liquid to collect the solid; washing and drying the solid in turn to obtain the sheet Ti3C2T x In the present invention, the Ti3C2T x Preferably a single piece of Ti3C2T x or multiple pieces of Ti3C2T x .
[0036] In the present invention, Ti3C2T x Particles as raw materials, Ti3C2T x There are a large number of functional groups on the surface of the particles, which can easily form composite materials with ZIF-62.
[0037] Get Ti3C2T flakes x After that, the present invention converts the sheet Ti3C2T x , zinc salt and an organic solvent (referred to as the first organic solvent) are mixed to obtain a zinc salt solution.
[0038] In the present invention, the zinc salt preferably includes zinc acetate or zinc nitrate, and more preferably zinc acetate. In the present invention, the first organic solvent preferably includes N,N-dimethylformamide (DMF).
[0039] In the present invention, the Ti3C2T x The mass ratio of the Ti3C2T4 layer to the zinc salt is preferably 5 to 15:1, and more preferably 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1 or 15:1. x The usage ratio of the first organic solvent is preferably 1 g:50-100 mL, specifically preferably 1 g:50 mL, 1 g:60 mL, 1 g:70 mL, 1 g:80 mL, 1 g:90 mL or 1 g:100 mL.
[0040] In the present invention, the Ti3C2T xThe mixing of the zinc salt and the organic solvent is preferably carried out under stirring, and the stirring speed is preferably 600-1200 rpm, specifically preferably 600 rpm, 700 rpm, 800 rpm, 900 rpm, 1000 rpm, 1100 rpm or 1200 rpm; the time is preferably 1-12 h, more preferably 1 h, 2 h, 5 h, 6 h, 8 h, 9 h, 10 h or 12 h.
[0041] The invention dissolves imidazole and benzimidazole to obtain a ligand solution.
[0042] In the present invention, the solvent in which the imidazole and benzimidazole are dissolved is preferably an organic solvent (referred to as the second organic solvent), and the second organic solvent preferably includes N,N-dimethylformamide (DMF).
[0043] In the present invention, the mass ratio of imidazole to benzimidazole is preferably 3 to 12:1, specifically preferably 3:1, 4:1, 5:1, 5.2:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1 or 12:1.
[0044] In the present invention, the usage ratio of the imidazole to the second organic solvent is preferably 1.463 g:10-30 mL, specifically preferably 1.463 g:10 mL, 1.463 g:15 mL, 1.463 g:20 mL, 1.463 g:25 mL or 1.463 g:30 mL.
[0045] After obtaining the zinc salt solution and the ligand solution, the present invention adds the ligand solution to the zinc salt solution to perform an ultrasonic synthesis reaction to obtain ZIF-62 / Ti3C2T x Material.
[0046] In the present invention, the mass ratio of the zinc salt to imidazole is preferably 0.166:1-2, and specifically preferably 0.166:1, 0.166:1.463, 0.166:1.5 or 0.166:2.
[0047] In the present invention, the addition of the ligand solution is preferably carried out under ultrasonic conditions, and the frequency and temperature of the ultrasound are preferably consistent with the ultrasonic synthesis reaction described below, which will not be described in detail herein.
[0048] In the present invention, the ultrasonic frequency of the ultrasonic synthesis reaction is preferably 30-60 Hz, specifically preferably 30 Hz, 40 Hz, 50 Hz or 60 Hz; the temperature is preferably 20-60°C, specifically preferably 20°C, 30°C, 40°C, 50°C or 60°C; the time is preferably 2-6h, specifically preferably 2h, 3h, 4h, 5h or 6h. In the present invention, the time of the ultrasonic synthesis reaction is preferably started after the addition of the ligand solution is completed.
[0049] After the ultrasonic synthesis reaction, the present invention preferably further comprises: washing, centrifuging and drying the obtained ultrasonic synthesis reaction liquid in sequence to obtain the ZIF-62 / Ti3C2T x Materials. In the present invention, the washing reagent is preferably N,N-dimethylformamide (DMF). In the present invention, the drying temperature is preferably 60°C, the drying time is preferably 24 hours, and the drying is preferably carried out in a vacuum drying oven.
[0050] In the present invention, the ultrasonic synthesis reaction can make imidazole, benzimidazole and zinc salt form ZIF-62 in situ and insert it into the Ti3C2T x In the layer of ZIF-62, Ti3C2T x The interlayers play a supporting role and stabilize Ti3C2T x interlayer spacing, preventing Ti3C2T x Excessive swelling in aqueous solution improves separation performance.
[0051] Get ZIF-62 / Ti3C2T x After the material is prepared, the ZIF-62 / Ti3C2T x The material is calcined to obtain a g ZIF-62 / Ti3C2T x Material.
[0052] In the present invention, the calcination temperature is preferably 420-480°C, and is particularly preferably 420°C, 430°C, 440°C, 450°C, 460°C, 470°C or 480°C; the heating rate to the calcination temperature is preferably 5-15K / min, and is preferably 5K / min, 6K / min, 7K / min, 8K / min, 9K / min, 10K / min, 11K / min, 12K / min, 13K / min, 14K / min or 15K / min; the holding time is preferably 1-10min, and is particularly preferably 1min, 2min, 3min, 4min, 5min, 6min, 7min, 8min, 9min or 10min. In the present invention, the calcination is preferably carried out under a protective atmosphere, and the protective atmosphere is preferably argon. In the present invention, the calcination is preferably carried out in a tubular furnace.
[0053] After the calcination, the present invention preferably further comprises: cooling to room temperature with the furnace under the protection of a protective atmosphere to obtain the a g ZIF-62 / Ti3C2T x Material.
[0054] In the present invention, the calcination can make ZIF-62 / Ti3C2T x The ZIF-62 crystal particles in the material are vitrified to form vitrified ZIF-62 (a g ZIF-62); a g ZIF-62 further enhanced a g ZIF-62 / Ti3C2T x In the material g ZIF-62 for Ti3C2T x The pillar support and inter-layer stability further prevent a g ZIF-62 / Ti3C2T x The material overswells in aqueous solution, improving separation performance.
[0055] Get a g ZIF-62 / Ti3C2T x After the material, the present invention will be described a g ZIF-62 / Ti3C2T x The material, the modifier and water are mixed, and then modified and formed into a membrane in sequence to obtain the ceramic-based oil-water separation membrane.
[0056] In the present invention, the a g ZIF-62 / Ti3C2T x The material is preferably a g ZIF-62 / Ti3C2T x The material is used in the form of powder, the a g ZIF-62 / Ti3C2T x The particle size of the material powder is preferably less than or equal to 5 μm, and more preferably 5 μm.
[0057] In the present invention, the modifier preferably includes one or more of carboxymethyl cellulose (CMC), polyethylene glycol and chitosan, and more preferably carboxymethyl cellulose.
[0058] In the present invention, the water is preferably deionized water.
[0059] In the present invention, the a g ZIF-62 / Ti3C2T x The mass ratio of the material to the modifier is preferably 1 to 10:1, more preferably 1 to 5:1, specifically preferably 1:1, 1.6:1, 1.9:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1 or 10:1.
[0060] In the present invention, the a g ZIF-62 / Ti3C2T xThe usage ratio of the material and water is preferably 0.64 to 3.1 mg:50 mL, and specifically preferably 0.64 mg:50 mL, 1.33 mg:50 mL or 3.1 mg:50 mL.
[0061] In the present invention, the temperature of the modification is preferably room temperature, that is, no additional heating or cooling is required. In the present invention, the time of the modification is preferably 12 to 36 hours, and specifically preferably 12 hours, 18 hours, 24 hours, 30 hours or 36 hours. In the present invention, the modification is preferably carried out under stirring, and the stirring speed is preferably 600 to 1200 rpm, and specifically preferably 600 rpm, 700 rpm, 800 rpm, 900 rpm, 1000 rpm, 1100 rpm or 1200 rpm.
[0062] After the modification, the present invention preferably directly forms a membrane from the obtained modified liquid.
[0063] In the present invention, the film forming method is preferably vacuum filtration, the filter membrane used in the vacuum filtration is preferably a CMC membrane, and the pore size of the CMC membrane is preferably 0.45 μm.
[0064] After the film forming, the present invention preferably further comprises drying.
[0065] The present invention also provides a ceramic-based oil-water separation membrane prepared by the preparation method described in the above technical solution.
[0066] In the present invention, the ceramic-based oil-water separation membrane preferably comprises a base membrane and a composite material attached to the base membrane. In the present invention, the base membrane is preferably a CMC membrane, and the pore size of the CMC membrane is preferably 0.45 μm. In the present invention, the composite material is preferably a modified g ZIF-62 / Ti3C2T x Material.
[0067] The present invention also provides the application of the ceramic-based oil-water separation membrane described in the above technical solution in floating oil wastewater and oil-in-water emulsified wastewater.
[0068] In the present invention, the particle size of the emulsion droplets in the oil-in-water emulsified wastewater is preferably 50 to 200 nm, and the oil-in-water emulsified wastewater is a stable colloidal system.
[0069] The ceramic-based oil-water separation membrane provided by the present invention, its preparation method and application are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0070] Example 1
[0071] 1g Ti3C2T xThe particles were added to 15 mL of dimethyl sulfoxide and stirred at 800 rpm for 24 h. The collected solids were then washed and dried to obtain Ti3C2T x .
[0072] 1g of Ti3C2T x and 0.166 g of zinc acetate were added into 80 mL of N,N-dimethylformamide (DMF), and stirred at 800 rpm for 2 h to obtain a zinc salt solution.
[0073] 1.463 g of imidazole and 0.284 g of benzimidazole were weighed and added into 20 mL of DMF to dissolve to obtain a ligand solution.
[0074] Under the condition of ultrasonic treatment, the ligand solution was added to the zinc salt solution to carry out ultrasonic synthesis reaction. The ultrasonic frequency of the ultrasonic synthesis reaction was 40 Hz, the temperature was 20 ° C, and the time was 4 h. After the ultrasonic synthesis reaction, it was washed with DMF and centrifuged. The obtained solid was dried in a vacuum drying oven at 60 ° C for 24 h to obtain ZIF-62 / Ti3C2T x Material.
[0075] Weigh 0.1 g ZIF-62 / Ti3C2T x The material was placed in an argon protected tubular furnace for calcination, and the ZIF-62 / Ti3C2T x The ZIF-62 crystal particles in the material are vitrified to obtain a g ZIF-62 / Ti3C2T x The material is specifically: the heating rate is controlled at 10K / min, the calcination temperature is 450°C, and the temperature is kept for 5 minutes; after calcination, it is cooled to room temperature with the furnace under argon protective atmosphere and then taken out.
[0076] A g ZIF-62 / Ti3C2T x The material was ground to obtain a particle size of 5 μm. g ZIF-62 / Ti3C2T x Material powder.
[0077] Weigh 0.64 mg of a with a particle size of 5 μm g ZIF-62 / Ti3C2T x The material powder and 0.34 mg CMC were added to 50 mL deionized water and stirred at 800 rpm for 24 h. After modification, the modified liquid was transferred to a vacuum filtration device, and vacuum filtered on the surface of a commercial CMC membrane with a pore size of 0.45 μm to form a membrane and dried to obtain a ceramic-based oil-water separation membrane.
[0078] 0.2 g of sodium dodecyl sulfate and 2 g of lubricating oil were added to 200 mL of deionized water and stirred for 1 hour to obtain a stable oil-in-water emulsified wastewater, wherein the particle size of the emulsion droplets was 50 to 200 nm.
[0079] Under vacuum filtration, the prepared ceramic-based oil-water separation membrane is used to treat oil-in-water emulsified wastewater.
[0080] By analyzing the TOC results, it was found that the oil-water separation efficiency of the ceramic-based oil-water separation membrane could reach 98.34%, and the flux was 882.00 L·m -2 ·h -1 .
[0081] Example 2
[0082] 1g Ti3C2T x The particles were added to 15 mL of dimethyl sulfoxide and stirred at 800 rpm for 24 h. The collected solids were then washed and dried to obtain Ti3C2T x .
[0083] 1g of Ti3C2T x and 0.166 g of zinc acetate were added into 80 mL of N,N-dimethylformamide (DMF) solution and stirred at 800 rpm for 2 h to obtain a zinc salt solution.
[0084] 1.463 g of imidazole and 0.284 g of benzimidazole were weighed and added into 20 mL of DMF to dissolve to obtain a ligand solution.
[0085] Under the condition of ultrasonic treatment, the ligand solution was added to the zinc salt solution to carry out ultrasonic synthesis reaction. The ultrasonic frequency of the ultrasonic synthesis reaction was 40 Hz, the temperature was 20 ° C, and the time was 4 h. After the ultrasonic synthesis reaction, it was washed with DMF and centrifuged. The obtained solid was dried in a vacuum drying oven at 60 ° C for 24 h to obtain ZIF-62 / Ti3C2T x Material.
[0086] Weigh 0.1 g ZIF-62 / Ti3C2T x The material was placed in an argon protected tubular furnace for calcination, and the ZIF-62 / Ti3C2T x The ZIF-62 crystal particles in the material are vitrified to obtain a g ZIF-62 / Ti3C2T x The material is specifically as follows: the heating rate is controlled at 10K / min, the calcination temperature is 450°C, and the temperature is kept for 5 minutes. After calcination, it is cooled to room temperature with the furnace under an argon protective atmosphere and then taken out.
[0087] Ag ZIF-62 / Ti3C2T x The material was ground to obtain a particle size of 5 μm. g ZIF-62 / Ti3C2T x Material powder.
[0088] Weigh 3.1 mg of a with a particle size of 5 μm g ZIF-62 / Ti3C2T x The material powder and 1.9 mg CMC were added to 50 mL deionized water and stirred at 800 rpm for 24 h. After modification, the modified liquid was transferred to a vacuum filtration device, and vacuum filtered on the surface of a commercial CMC membrane with a pore size of 0.45 μm to form a membrane and dried to obtain a ceramic-based oil-water separation membrane.
[0089] 0.25 g of sodium dodecyl sulfate and 1 g of lubricating oil were added to 200 mL of deionized water and stirred for 1 hour to obtain a stable oil-in-water emulsified wastewater, wherein the particle size of the emulsion droplets was 50 to 200 nm.
[0090] Under vacuum filtration, the prepared ceramic-based oil-water separation membrane is used to treat oil-in-water emulsified wastewater.
[0091] By analyzing the TOC results, it was found that the oil-water separation efficiency of the ceramic-based oil-water separation membrane could reach 99.84%, and the flux was 63.76 L·m -2 ·h -1 .
[0092] Example 3
[0093] 1g Ti3C2T x The particles were added to 15 mL of dimethyl sulfoxide and stirred at 800 rpm for 24 h. The collected solids were then washed and dried to obtain Ti3C2T x .
[0094] 1g of Ti3C2T x and 0.166 g of zinc acetate were added into 80 mL of N,N-dimethylformamide (DMF), and stirred at 800 rpm for 2 h to obtain a zinc salt solution.
[0095] 1.463 g of imidazole and 0.284 g of benzimidazole were weighed and added into 20 mL of DMF to dissolve to obtain a ligand solution.
[0096] Under the condition of ultrasonic treatment, the ligand solution was added to the zinc salt solution to carry out ultrasonic synthesis reaction. The ultrasonic frequency of the ultrasonic synthesis reaction was 40 Hz, the temperature was 20 ° C, and the time was 4 h. After the ultrasonic synthesis reaction, it was washed with DMF and centrifuged. The obtained solid was dried in a vacuum drying oven at 60 ° C for 24 h to obtain ZIF-62 / Ti3C2T x Material.
[0097] Weigh 0.1 g ZIF-62 / Ti3C2T x The material was placed in an argon protected tubular furnace for calcination, and the ZIF-62 / Ti3C2T x The ZIF-62 crystal particles in the material are vitrified to obtain a g ZIF-62 / Ti3C2T x The material is specifically as follows: the heating rate is controlled at 10K / min, the calcination temperature is 450°C, and the temperature is kept for 5 minutes. After calcination, it is cooled to room temperature with the furnace under an argon protective atmosphere and then taken out.
[0098] A g ZIF-62 / Ti3C2T x The material was ground to obtain a particle size of 5 μm. g ZIF-62 / Ti3C2T x Material powder.
[0099] Weigh 1.33 mg of a with a particle size of 5 μm g ZIF-62 / Ti3C2T x The material powder and 0.67 mg CMC were added to 50 mL deionized water and stirred at 800 rpm for 24 h. After modification, the modified liquid was transferred to a vacuum filtration device, and vacuum filtered on the surface of a commercial CMC membrane with a pore size of 0.45 μm to form a membrane and dried to obtain a ceramic-based oil-water separation membrane.
[0100] 0.005 g of Sudan III was dissolved in 50 mL of n-hexane and mixed with 50 mL of deionized water to obtain layered oily wastewater.
[0101] Under vacuum filtration, the prepared ceramic-based oil-water separation membrane was used to treat stratified floating oil wastewater, and it was found that water and n-hexane could be easily separated. By analyzing the TOC results, it was found that the oil-water separation efficiency of the ceramic-based oil-water separation membrane could reach 99.99%.
[0102] Comparative Example 1
[0103] 0.2 g of sodium dodecyl sulfate and 2 g of lubricating oil were added to 200 mL of deionized water and stirred for 1 hour to obtain a stable oil-in-water emulsified wastewater, wherein the particle size of the emulsion droplets was 50 to 200 nm.
[0104] Directly use commercial CMC membrane to treat oil-in-water emulsified wastewater.
[0105] By analyzing the TOC results, it was found that the oil-water separation efficiency of the CMC membrane could reach 71.36%, and the flux was 140.50 L·m -2 ·h -1 .
[0106] 0.005 g of Sudan III was dissolved in 50 mL of n-hexane and mixed with 50 mL of deionized water to obtain layered oily wastewater.
[0107] When commercial CMC membrane was used directly to treat stratified oily wastewater, it was found that the oily wastewater could not be separated well and a dyed oil phase existed in the water phase.
[0108] Comparative Example 2
[0109] According to the method of Example 1, ZIF-62 / Ti3C2T x Material.
[0110] ZIF-62 / Ti3C2T x The material was ground to obtain ZIF-62 / Ti3C2T with a particle size of 5 μm. x Material powder.
[0111] 5 mg ZIF-62 / Ti3C2T with a particle size of 5 μm was added x The material powder was dispersed in 100 mL of deionized water. After being fully dispersed, the dispersion was transferred to a vacuum filtration device, and vacuum filtered on the surface of a commercial CMC membrane with a pore size of 0.45 μm to form a membrane and dried to obtain a ceramic-based oil-water separation membrane.
[0112] 0.2 g of sodium dodecyl sulfate and 2 g of lubricating oil were added to 200 mL of deionized water and stirred for 1 hour to obtain a stable oil-in-water emulsified wastewater, wherein the particle size of the emulsion droplets was 50 to 200 nm.
[0113] By analyzing the TOC results, it was found that the oil-water separation efficiency of the ceramic-based oil-water separation membrane could reach 87.32%, and the flux was 81.00 L·m -2 ·h -1 .
[0114] Comparative Example 3
[0115] According to the method of Example 1, a particle size of 5 μm was obtained. g ZIF-62 / Ti3C2T x Material powder.
[0116] 5 mg of a with a particle size of 5 μm gZIF-62 / Ti3C2T x The material powder was dispersed in 100 mL of deionized water. After being fully dispersed, the dispersion was transferred to a vacuum filtration device, and vacuum filtered on the surface of a commercial CMC membrane with a pore size of 0.45 μm to form a membrane and dried to obtain a ceramic-based oil-water separation membrane.
[0117] 0.2 g of sodium dodecyl sulfate and 2 g of lubricating oil were added to 200 mL of deionized water and stirred for 1 hour to obtain a stable oil-in-water emulsified wastewater, wherein the particle size of the emulsion droplets was 50 to 200 nm.
[0118] By analyzing the TOC results, it was found that the oil-water separation efficiency of the ceramic-based oil-water separation membrane could reach 91.07%, and the flux was 90.07 L·m -2 ·h -1 .
[0119] In summary, the ceramic-based oil-water separation membrane prepared by the present invention is suitable for the efficient separation of oil and water in stable emulsified wastewater and floating oil wastewater. Moreover, the raw materials for preparing the ceramic-based oil-water separation membrane are widely available and the operation method is simple, which can provide a new direction for the oil-water separation industry and make positive contributions to reducing material consumption.
[0120] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a ceramic-based oil-water separation membrane, characterized in that: The following steps are involved: Ti3C2T x The particles are peeled off to obtain Ti3C2T flakes. x ; The Ti3C2T x , zinc salt and an organic solvent are mixed to obtain a zinc salt solution; dissolving imidazole and benzimidazole to obtain a ligand solution; The ligand solution is added to the zinc salt solution to perform an ultrasonic synthesis reaction to obtain ZIF-62 / Ti3C2T x Material; The ZIF-62 / Ti3C2T x The material is calcined to obtain a g ZIF-62 / Ti3C2T x Material; The a g ZIF-62 / Ti3C2T x The material, the modifier and water are mixed, and then modified and formed into a membrane in sequence to obtain the ceramic-based oil-water separation membrane.
2. The preparation method according to claim 1, characterized in that: The stripping comprises: removing the Ti3C2T x The particles are dispersed in dimethyl sulfoxide and chemically intercalated to obtain the Ti3C2T x ; The Ti3C2T x The dosage ratio of the particles to dimethyl sulfoxide is 1 g: 10-20 mL; the chemical intercalation is carried out under stirring conditions, the stirring speed is 600-1200 rpm, and the time is 18-30 hours.
3. The preparation method according to claim 1, characterized in that: The zinc salt includes zinc acetate or zinc nitrate; the sheet Ti3C2T x The mass ratio of zinc salt to zinc salt is 5 to 15:
1.
4. The preparation method according to claim 1, characterized in that: The mass ratio of the imidazole to the benzimidazole is 3 to 12:
1.
5. The preparation method according to claim 1, characterized in that: The ultrasonic synthesis reaction has an ultrasonic frequency of 30 to 60 Hz, a temperature of 20 to 60° C., and a time of 2 to 6 hours.
6. The preparation method according to claim 1, characterized in that: The calcination temperature is 420-480° C., the heating rate to the calcination temperature is 5-15 K / min, and the heat preservation time is 1-10 min.
7. The preparation method according to claim 1, characterized in that: The modifier comprises one or more of carboxymethyl cellulose, polyethylene glycol and chitosan, wherein a g ZIF-62 / Ti3C2T x The mass ratio of the material to the modifier is 1 to 10:1; The modification time is 12 to 36 hours.
8. The preparation method according to claim 1, characterized in that: The film forming method is vacuum filtration, and the filter membrane used in the vacuum filtration is a CMC membrane, and the pore size of the CMC membrane is 0.45 μm.
9. A ceramic-based oil-water separation membrane obtained by the preparation method according to any one of claims 1 to 8.
10. Use of the ceramic-based oil-water separation membrane according to claim 9 in oily wastewater and oil-in-water emulsified wastewater.
Citation Information
Patent Citations
Method for preparing MOF nanofiltration membrane by adopting thermal annealing post-synthesis technology
CN111672330A
Two-dimensional MXene-based oil-water separation membrane and preparation method thereof
CN114272766A
Graphene-assisted MOF (Metal Organic Framework) membrane material for extracting helium from natural gas as well as preparation method and application of graphene-assisted MOF membrane material
CN115672062A
ZIF-8 / GO composite membrane as well as preparation method and application thereof
CN115722084A
Single-layer or few-layer MXene material as well as preparation method and application thereof
CN118454475A
Cited By
Preparation method of PTFE oil-water separation composite membrane
CN120169178A
A method for preparing a PTFE oil-water separation composite membrane
CN120169178B